2016
DOI: 10.1111/acps.12671
|View full text |Cite
|
Sign up to set email alerts
|

Infections and exposure to anti‐infective agents and the risk of severe mental disorders: a nationwide study

Abstract: Infections treated with anti-infective agents and particularly infections requiring hospitalizations were associated with increased risks of schizophrenia and affective disorders, which may be mediated by effects of infections/inflammation on the brain, alterations of the microbiome, genetics, or other environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 33 publications
7
69
0
1
Order By: Relevance
“…These findings are consistent with a growing body of evidence for increased risk of adult mental disorder among offspring of mothers exposed to infection during pregnancy (Brown, ; Hamdani et al., ; Jablensky et al., ; Selten & Morgan, ), as well as individuals exposed to infectious and autoimmune diseases throughout the life course (Abrahao et al., ; Benros et al., , ; Blomstrom et al., ; Dalman et al., ; Kohler et al., ; Koponen et al., ). Among all of the risk exposures examined here, the highest odds of developmental vulnerability were observed for offspring exposed to maternal mental illness first diagnosed prior to the child's birth, suggesting a possible role for inherited genetic susceptibility to mental disorder, rather than the effects of stress on the child that may be associated with being exposed to the behavior of a mentally ill mother during the early childhood years.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings are consistent with a growing body of evidence for increased risk of adult mental disorder among offspring of mothers exposed to infection during pregnancy (Brown, ; Hamdani et al., ; Jablensky et al., ; Selten & Morgan, ), as well as individuals exposed to infectious and autoimmune diseases throughout the life course (Abrahao et al., ; Benros et al., , ; Blomstrom et al., ; Dalman et al., ; Kohler et al., ; Koponen et al., ). Among all of the risk exposures examined here, the highest odds of developmental vulnerability were observed for offspring exposed to maternal mental illness first diagnosed prior to the child's birth, suggesting a possible role for inherited genetic susceptibility to mental disorder, rather than the effects of stress on the child that may be associated with being exposed to the behavior of a mentally ill mother during the early childhood years.…”
Section: Discussionsupporting
confidence: 83%
“…The primacy of infectious agents in conferring risk for later mental disorders should therefore not be assumed. Moreover, comparable increases in risk for schizophrenia and mood disorders are also associated with exposure to infection during childhood (Abrahao, Focaccia, & Gattaz, ; Benros et al., , ; Blomstrom et al., ; Dalman et al., ; Kohler et al., ; Koponen et al., ; Liang & Chikritzhs, ) and adolescence (Nielsen, Benros, & Mortensen, ; Nielsen, Laursen, & Mortensen, ; Sorensen et al., ), suggesting that events in developmental periods other than gestation also contribute to risk of mental disorders. Indeed, two recent studies have reported small but significant associations between early childhood vulnerability indicators and childhood infection (Kariuki et al., ), as well as with other chronic health conditions (Bell, Bayliss, Glauert, Harrison, & Ohan, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The urinary tract was the most common site of infection in women while the respiratory tract and mucosal surfaces were the most common sites in men. An association between antibiotic exposure and mood disorder has also been found in population based studies performed in the United Kingdom (Lurie, Yang, Haynes, Mamtani, & Boursi, 2015) and Denmark (Kohler et al, 2016). …”
Section: Resultsmentioning
confidence: 68%
“…A recent study found an excess risk of severe adult mental disorders among individuals with infections treated with antibiotics, with the most pronounced effects observed for broad‐spectrum and moderate‐spectrum antibiotics [Kohler et al, ]. Another population‐based cohort study indicated an association between maternal use of antibiotics during pregnancy and development of autism in the child [Atladottir, Henriksen, Schendel, & Parner, ; Sharon et al, ].…”
Section: Introductionmentioning
confidence: 99%